The Effect of Special Vital Exercises to Force the Opposing Team to Commit Mistakes and Legal Irregularities in Handball - Thaerah Abdul Jabbar Saleh (Journal of Global Pharma Technology, 2018)
That the multiplicity of skills and plans offensive individual and collective handball players was also accompanied by the development of defensive aspects, which led researchers to use and experimenting methods that are highly influential on the performance of individual defense and collective and offensive, so the importance of research by finding some exercises, The ball directly, but also affect the competitor and push him to commit errors and legal irregularities to benefit from the contribution studied in the increase of penalties and progressive suspension cases . In this case, the problem of research was not to exploit the imposition of individual and individual punishments imposed by the law, but to limit the interest in directing the players not to make these irregularities and mistakes to avoid penalties. Therefore, exercises were put in place for forcing the players of the opposing team to commit violations and legal errors. The effect of some exercises in forcing the opposing team players to commit mistakes and legal irregularities the researchers hypothesized that there were significant differences between the tribal and remote tests of the two groups and for the benefit of the remote tests. There were also significant differences between the tests of the two groups of research and for the experimental group. The researchers used the experimental method. The research community was determined by the players of the Karbala University team for the academic year 2011/2012 and for the Karbala youth handball players for the handball at the age of 18-20 years. A sample of (30) players from this society were selected and divided equally into two control groups. The results came in favor of the experimental group, and the researchers concluded that the special exercises used were of interest to the players in forcing the opposing team to commit legal errors and irregularities. This type of exercise has a great positive impact on the outcome of the game and thus achievement especially for players of age groups. The researchers recommended that trainers adopt this type of exercise in their training and use it for younger age groups, which are likely to have greater results because they are less aware of the law and its applications.Keywords: Vital exercises, force, opposing team, commit mistakes and legal irregularities.